A content analysis of media coverage on road safety and road traffic crashes in Colombia - Saporito, Kristi; Rothenstein-Henry, Rachel; Zeynalova, Elizaveta; Negi, Nalin Singh; Mullin, Sandra; Morozova, Irina; Murukutla, Nandita (Frontiers in Future Transportation, 2023)
In Colombia, road traffic crashes are the eighth leading cause of death. In 2017, as part of the Bloomberg Philanthropies Initiative for Global Road Safety (BIGRS), Vital Strategies supported government-led journalist trainings in Colombia to shift media discourse of road safety as a public health and development issue with known risk factors and achievable solutions, to ultimately catalyze public and policymaker concern and action. This study evaluates the effects these trainings had on road safety reporting. Articles about BIGRS road safety work published between May 1, 2017 and Aug. 30, 2021 were collected from a database maintained by communication officers. The sample included 870 articles, which were systematically analyzed for year-wise frequency by independent coders. Inter-reliability (Cohen’s Kapp K > 0.94) was established using a codebook developed to identify examples of best practices shared during trainings. From 2017 to 2021, there was a 27% increase in articles that situated road traffic collisions (RTCs) as due to systemic issues (thematic framing) rather than isolated events (episodic framing). Almost all observed articles used at least one WHO-recommended story angle (96%) and key element (95%). Reporting angles focused on the human story were largely underutilized (2-5%). Government representatives (81%), mostly from the Secretary of Mobility (67%), were the most cited sources and road safety advocates were the least (3%). Use of terms “crash” and “collision” increased across the study period (crash: 47% in 2017 to 59% in 2021; collision: 0.4% in 2019 to 5% in 2020). However, RTCs continued to be widely called “accidents” (46%). More than half of articles referenced either “victims” or “vulnerable road users” (55%); use of “person” to refer to victims/vulnerable road users increased from 33% in 2017 to 56% in 2020. Over the course of the BIGRS journalist training program, reporting in Colombia increasingly used best practices to frame road safety as a public health issue. This highlights how media engagement is important to comprehensive road safety strategies and should be more widely adopted. Future training efforts should focus on finding the human story, and on changing overreliance on terms like “accident” that make RTCs seem inevitable.